Diffrential Diagnosis of Hepatic Hydrothorax by (99m)Tc Sulfur Colloid Peritoneal Scintigraphy: Two Cases - Aygun, Cem (Gastroenterology Res, 2009)
Large symptomatic pleural effusions can be seen in cirrhotic patients with ascites. In this report, two cirrhotic patients with ascites and large pleural effusions were evaluated. To determine the cause of pleural effusion and to understand whether there was a communication of fluid between peritoneal and pleural cavities, (99m)Tc sulfur colloid peritoneal scintigraphy was used. According to the scintigraphic results, the diagnosis of hepatic hydrothorax and tuberculosis was confirmed easily and the treatments of the patients were managed rapidly.